Nudge or Grudge? Choice Architecture and Parental Decision-Making - Blumenthal-Barby, Jennifer (The Hastings Center report, 2018)
Richard Thaler and Cass Sunstein define a nudge as “any aspect of the choice architecture that alters people's behavior in a predictable way without forbidding any options or significantly changing their economic incentives.” Much has been written about the ethics of nudging competent adult patients. Less has been written about the ethics of nudging surrogates’ decision-making and how the ethical considerations and arguments in that context might differ. Even less has been written about nudging surrogate decision-making in the context of pediatrics, despite fundamental differences that exist between the pediatric and adult contexts. Yet, as the field of behavioral economics matures and its insights become more established and well-known, nudges will become more crafted, sophisticated, intentional, and targeted. Thus, the time is now for reflection and ethical analysis regarding the appropriateness of nudges in pediatrics. We argue that there is an even stronger ethical justification for nudging in parental decision-making than with competent adult patients deciding for themselves. We give three main reasons in support of this: (1) child patients do not have autonomy that can be violated (a concern with some nudges), and nudging need not violate parental decision-making authority; (2) nudging can help fulfill pediatric clinicians’ obligations to ensure parental decisions are in the child's interests, particularly in contexts where there is high certainty that a recommended intervention is low risk and of high benefit; and (3) nudging can relieve parents’ decisional burden regarding what is best for their child, particularly with decisions that have implications for public health.